The effect of misoprostol on fetal heart rate parameters during induction of labour from 38 weeks gestation : a retrospective audit - Feketshane, Anthony M. (Stellenbosch : Stellenbosch University, 2013)
Thesis (MMed)-- Stellenbosch University, 2013.